2022
DOI: 10.1029/2021jd036011
|View full text |Cite
|
Sign up to set email alerts
|

MJO Phase Swings Modulate the Recurring Latitudinal Shifts of the 2020 Extreme Summer‐Monsoon Rainfall Around Yangtse

Abstract: Considering the unprecedented extremity of the Meiyu episodes in early summer of 2020, here the authors perform a comprehensive study of the intraseasonal evolution characteristics of the observed rainfall round Yangtse as well as the potential modulating effect of Madden‐Julian Oscillation (MJO). Results suggest that the Meiyu rainfall manifests as recurring latitudinal shifts around Yangtse during June–July of 2020, corresponding well to the continued swings of MJO circulation and convection between Phase 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Hydroclimate extremes driven by the ASM are no exception and may change in a warming climate (Rajesh & Goswami, 2022; Saranya et al., 2022; Sarkar & Maity, 2022). Both strong and weak monsoons have the potential to critically disrupt agriculture, damage infrastructure via flooding, and impact water supply (Wang et al., 2022). Generating a more robust understanding of future hydroclimate extremes in the ASM region depends on accurate statistics surrounding the role of natural variability in modulating rainfall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroclimate extremes driven by the ASM are no exception and may change in a warming climate (Rajesh & Goswami, 2022; Saranya et al., 2022; Sarkar & Maity, 2022). Both strong and weak monsoons have the potential to critically disrupt agriculture, damage infrastructure via flooding, and impact water supply (Wang et al., 2022). Generating a more robust understanding of future hydroclimate extremes in the ASM region depends on accurate statistics surrounding the role of natural variability in modulating rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…
The Asian summer monsoon (ASM) supplies freshwater resources for nearly 4 billion people annually. Its variations and related hydroclimate events cause floods and droughts, which have far-reaching social and economic impacts, especially in countries that are heavily dependent on agriculture (Gadgil & Kumar, 2006;Loo et al, 2015;Wang et al, 2022). Climate change is expected to change the characteristics of the ASM (Rajesh & Goswami, 2022); dry and hot monsoon extremes are expected to occur more frequently alongside future warming (Mishra et al, 2020), in addition to the increased risk of flash flooding (Almazroui et al, 2021).
…”
mentioning
confidence: 99%
“…Particularly in July 2020, the long-standing MJO in the Indian Ocean favored the WNP anomalous low-level anticyclone (e.g., Gong et al, 2022) but this is not the case for June. Wang et al (2022) noted that the convective episode associated with MJO in July slowly propagated eastward and decayed when encountering the Maritime Continent barrier effect (Zhang & Ling, 2017). This event comes under the non-propagating MJO convection event (Kim et al, 2014).…”
Section: Changes In Sst and Low-level Circulationmentioning
confidence: 99%
“…suggested that an unprecedented long-standing MJO occurred in the Indian Ocean during early summer. Wang et al (2022) showed that the MJO had modulated the latitudinal position and intensity of the anomalous anticyclone over the WNP. Particularly in July 2020, the long-standing MJO in the Indian Ocean favored the WNP anomalous low-level anticyclone (e.g., Gong et al, 2022) but this is not the case for June.…”
Section: Changes In Sst and Low-level Circulationmentioning
confidence: 99%
“…The convection and upper‐tropospheric divergence of MJO activities also act as a Rossby wave source and stimulate the teleconnection between Tropics and mid‐latitudes on an intraseasonal timescale. In addition, they can further modulate the modes of extratropical climate variability and weather patterns, such as the North Atlantic Oscillation, Pacific‐North American pattern, blockings and extreme flooding and drought events (Stan et al ., 2017; Li et al ., 2020; Wang et al ., 2022). Due to its periodic nature and significant impacts, the MJO is a primary predictability source on a subseasonal timescale (Merryfield et al ., 2020) and provides windows of opportunity for skilful predictions during its active periods (Mariotti et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%